PRENATAL HUMANIZATION IN THE FAMILY HEALTH STRATEGY - Moura Nascimento de Andrade, Marta Rejane; de Lira Silva, Macerlane; do Nascimento Andrade Feitosa, Ankilma; Ruston Oliveira Braga, Thárcio (Health and Society, 2023)
Introduction: In summary, the humanization of prenatal care has the bias of ensuring gestational development, so that the delivery of the newborn is based on a process considered healthy, without impacting on women’s health, addressing aspects psychological and social, as well as preventive and educational activities. Objective: To address the importance of humanization in prenatal care in the Family Health Strategy. Methodology: The present study is an integrative literature review, being a method that enables the construction of knowledge and the inclusion of the applicability of results from relevant studies in the practical field. To elaborate the research corpus, queries were made to scientific databases on the internet: Scientific Electronic Library Online (SciELO), MEDLINE and LILACS. The Descriptors in Health Sciences were used to aid the results: Primary Care, Humanization, Pregnancy and Prenatal Care. Results and discussions: From the analysis of the literature, it can be seen the main outcomes about the importance of humanizing prenatal care in the Family Health Strategy. In this outcome, prenatal care is essential for health education and counseling on coping with the different aspects that restrict pregnancy, being steps that may involve the importance of healthy eating and physical activity, in addition to screening tests, what is expected from labor, approach in the face of possible risks, situating the woman on fundamental issues to the referred period experienced. Conclusion: In view of this, this study can verify the importance of humanized care in health services, for pregnant women, during prenatal consultations. From the results obtained, it can be seen that the objective outlined for this study was achieved.